Efeitos genéticos na longevidade de sementes de milho - Mota, Armando Dornelas (2015)
The present study has the objective of clarifying the genetic effect of maternal and paternal genitors over the physiological quality of hybrid corn seeds over time; in addition to the contribution of heterosis for such trait. To achieve this, eight genitors with contrasting and previously known traits for seed quality were selected. The simple hybrid, reciprocal, and genitor seeds used for conducting the experiment were obtained by means of manual crosses in a complete diallel scheme. After harvesting and processing, the seeds were submitted to germination and accelerated growth tests in a completely randomized design. We used the Tukey test at 5% probability to compare the means of the germination and accelerated growth tests. To analyze the data obtained from the accelerated growth test we used the Griffing method (1956), model I, with n2 possible numbers of genotypes. We verified that all sources of variation were highly significant (P≤0.01) for all evaluation periods. The quadratic components of the GCA were similar to the effects of the SCA and superior to reciprocals in most evaluation periods, inferring that the effects on seed quality traits were attributed to additive effect genes (GCA) and to nonadditive effect genes (SCA). The maternal effect was highly significant despite its contribution being inferior to that of GCA and SCA. However, it was presented as important in the combinations between genitors with a low GCA estimate.